PWE-092 Symptom Response Following Advice On A Diet Low In Short-chain Fermentable Carbohydrates (fodmaps) For Functional Bowel Symptoms In Patients With Ibd. (9th June 2014) - Joyce, T; Staudacher, H; Whelan, K; Irving, P; Lomer, M
Abstract : Introduction: The low FODMAP diet is an effective dietary intervention for people with functional bowel disorders (FBD), which are common in patients with inflammatory bowel disease (IBD). One study has reported that half of patients with IBD report improvements in abdominal pain, bloating, flatulence and diarrhoea after following a low FODMAP diet. Up to 70% of patients reported adherence to the diet. We aimed to assess the effectiveness of low FODMAP diet advice in patients with IBD in the UK. Methods: Patients with inactive IBD and FBD (as diagnosed by their gastroenterologist), who had been referred to the dietitian and advised on a low FODMAP diet were included in this evaluation of clinical practice. Symptoms were measured pre and post (at least 6 weeks) low FODMAP dietary advice as part of normal clinical practice using the global symptom question (GSQ)'Do you currently have satisfactory relief of your gut symptoms?' and the gastrointestinal symptom rating scale (GSRS). Stool frequency was considered 'normal' if between 2–3 times per week to 2–3 times per day. Types 3–5 on the Bristol stool form scale were considered normal stool consistency. Comparisons were made using the McNemar test for categorical data and a paired t-test for continuous data. Results: Data from 35 patients with IBD (17 ulcerative colitis, 17 Crohn's disease, one IBD unclassified, 63% female, mean age 39y) were analysed. There was a significant increase in the number of patients reporting positively to the GSQ (n[%] pre: 8 [23] versus post: 29 [83]; p < 0.001) and the GSRS composite score (mean [SD] pre: 1.25 [0.48] versus post: 0.77 [0.45]; p < 0.001). Fewer patients reported symptoms including abdominal pain, bloating, flatulence and urgency, increased stool frequency, and type 6 or 7 Bristol stool form post dietary advice compared with pre dietary advice (Table). Conclusion: The low FODMAP diet appears to be an effective treatment option for patients with IBD and FGD particularly for those with symptoms of abdominal bloating, flatulence, faecal urgency and lethargy. However, this is an evaluation of clinical practice and prospective randomised controlled evidence in IBD is currently lacking. Disclosure of Interest: None Declared.